The influence of savory on colour, odour and taste of frankfurters. Issue 1 (October 2021) - Karan, D; Lukic, M; Djordjevic, V; Parunovic, N; Babic Milijasevic, J; Jovanovic, J; Nikolic, A
Abstract: The aim of this paper was to assess the influence of savory on colour, odour and taste of vacuum-packed frankfurters during 28 days of storage. Powdered, dried savory (0.1%, 0.3% and 0.5%) was added to frankfurters, while control frankfurters were produced without herbs or spices. Assessment of colour, odour and taste acceptability of the frankfurters was performed by a panel of five assessors using a quantitative descriptive test, and the results of the ranking test were analysed statistically. When used at the levels of 0.1% and 0.3% in the sausages, savory did not have a negative influence on frankfurter colour, while quantities of 0.5% adversely affected frankfurter colour. Savory in the smaller amounts of 0.1% and 0.3% stimulated development of a pleasant odour and taste in the frankfurters, while 0.5% savory had an undesirable effect on these sensory attributes.